2014
DOI: 10.1111/febs.12656
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide expressional and functional analysis of calcium transport elements during abiotic stress and development in rice

Abstract: Ca2+ homeostasis is required to maintain a delicate balance of cytosolic Ca2+ during normal and adverse growth conditions. Various Ca2+ transporters actively participate to maintain this delicate balance especially during abiotic stresses and developmental events in plants. In this study, we present a genome‐wide account, detailing expression profiles, subcellular localization and functional analysis of rice Ca2+ transport elements. Exhaustive in silico data mining and analysis resulted in the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 92 publications
(129 reference statements)
4
92
0
Order By: Relevance
“…Investigators have demonstrated previously that ethylene interacts with 378 auxin, especially in the regulation of root growth (Růzicka et al, 2007;Swarup et al, 379 2007; Strader et al, 2010). In addition, seedlings of the BR-deficient mutant det2-1 380 and the BR-insensitive mutant bin2-1 have increased sensitivity to salt stress (Zeng et al, 2010 stress signaling in plants (Xiong et al, 2002;Singh et al, 2014;Ohama et al, 2017 microtubule arrays under salt stress (Ban et al, 2013;Fujita et al, 2013 …”
mentioning
confidence: 99%
“…Investigators have demonstrated previously that ethylene interacts with 378 auxin, especially in the regulation of root growth (Růzicka et al, 2007;Swarup et al, 379 2007; Strader et al, 2010). In addition, seedlings of the BR-deficient mutant det2-1 380 and the BR-insensitive mutant bin2-1 have increased sensitivity to salt stress (Zeng et al, 2010 stress signaling in plants (Xiong et al, 2002;Singh et al, 2014;Ohama et al, 2017 microtubule arrays under salt stress (Ban et al, 2013;Fujita et al, 2013 …”
mentioning
confidence: 99%
“…It is possible that the ER localisation of some GLRs (see Li et al 2006;Singh et al 2014) is a native feature and these receptors act as genuine ER receptors with a role in this Ca 2+ -enriched cellular compartment. In 2005, Meyerhoff et al (2005) showed for the first time a localisation of a GFP-tagged AtGLR at the plasma membrane of onion epidermal cells.…”
Section: Subcellular Localisationmentioning
confidence: 99%
“…Oryza sativa L. is another plant species in which GLRs are characterised. The rice genome encodes 24 different glutamate receptors (OsGLR) and they are very similar to AtGLRs of clade III Singh et al 2014). They cluster into four groups while group I, II and III seem to have a common ancestor with A. thaliana (Singh et al 2014).…”
Section: Glrs In Other Plant Speciesmentioning
confidence: 99%
See 2 more Smart Citations